1998
DOI: 10.1038/bjc.1998.566
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of nm23 to proteolytic factors, proliferation and motility in breast cancer tissues and cell lines

Abstract: Compared with the parent cell line, we did observe a dose-dependent decrease in growth factor-stimulated motility and a decrease in metastatic potential in two clones with four-and eighffold elevated nm23-H1 expression, whereas the proliferative activities were similar. We conclude that the decreased metastatic potential might be related to down-regulation of growth factor-stimulated motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…Eight di erent genes of this family have been identi®ed in humans (Lombardi et al, 2000), and their expression is linked to suppression of tumour metastasis, di erentiation, apoptosis, proliferation and DNA mutation (de la Rosa et al, 1995). NM23-H1 and -H2 are nucleoside diphosphate (NDP) kinases, and metastasis suppression was observed in several tumour cell lines transfected with nm23-H1 (Leone et al, 1991;Russell et al, 1998). Recently, it was reported that increased nm23-H1 expression, induced by an inhibitor of DNA methylation, reduced cell motility but had little e ect on cell proliferation (Hartsough et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Eight di erent genes of this family have been identi®ed in humans (Lombardi et al, 2000), and their expression is linked to suppression of tumour metastasis, di erentiation, apoptosis, proliferation and DNA mutation (de la Rosa et al, 1995). NM23-H1 and -H2 are nucleoside diphosphate (NDP) kinases, and metastasis suppression was observed in several tumour cell lines transfected with nm23-H1 (Leone et al, 1991;Russell et al, 1998). Recently, it was reported that increased nm23-H1 expression, induced by an inhibitor of DNA methylation, reduced cell motility but had little e ect on cell proliferation (Hartsough et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Therapies that specifically target metastatic suppressors are expected to suppress metastasis at a toxicity lower than that of conventional chemotherapies. 2 There are a number of metastatic suppressor candidates, such as intercellular communication factors (e.g., NM23-H1/H2, 3,4 KISS1, 5 and RHOGDI2 6 ), cell surface proteins and receptors (e.g., KAI1 [CD82] 7 ), and transcription factors (e.g., LSD1…”
Section: Introductionmentioning
confidence: 99%
“…11 In the case of human ovarian cancer, nm23 is related to the lymphatic dissemination of tumor cells and its expression has been suggested to be an independent prognostic factor. 2,12,13 Several experiments have shown that the exogenous expression of human nm23H1 results in a significant reduction of metastatic potential in vivo and impairment of cell migration ability in response to several cytokines in vitro. 2,8,13 Transfection of nm23 cDNA into metastatically competent breast carcinoma, 2,12,13 melanoma, 7,[14][15][16] colon carcinoma, 17 and oral squamous cell carcinoma cell lines 18 resulted in 40-98% decreased metastatic potential in vivo.…”
Section: Introductionmentioning
confidence: 99%